1994
DOI: 10.3109/15563659409011042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opiates on Blood Rheology

Abstract: To evaluate the possible effect of opiates on blood rheology, the plasma fibrinogen, prothrombin time and leukocyte aggregation were measured in 75 heroin addicts categorized by the time of abstention from heroin and the administration of naltrexone (25 active heroin abusers, 25 abstaining for 1 week, 11 abstaining for at least 5 months and 14 abstaining for 1 month and taking naltrexone during this period). No difference was detected in prothrombin time, but the leukocyte aggregation and fibrinogen were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…They found a significantly higher fibrinogen (318 ± 10.9 mg/dl) and different leukocyte aggregation in heroin abusers, but no difference was detected in prothrombin time among the studied groups [2].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…They found a significantly higher fibrinogen (318 ± 10.9 mg/dl) and different leukocyte aggregation in heroin abusers, but no difference was detected in prothrombin time among the studied groups [2].…”
Section: Discussionmentioning
confidence: 89%
“…To evaluate the possible effect of opiates on blood rheology Galante et al [2] measured the plasma fibrinogen, prothrombin time and leukocyte aggregation in 75 heroin addicts categorized by the time of abstention from heroin and the administration of naltrexone. They found a significantly higher fibrinogen (318 ± 10.9 mg/dl) and different leukocyte aggregation in heroin abusers, but no difference was detected in prothrombin time among the studied groups [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fibrinogen a-chain-derived peptide, fibrinopeptide A, was upregulated in response to morphine and spontaneous alternation. Although this appears to be the first report of fibrinogen level changes in rat brain, human studies have shown that opium users have higher fibrinogen blood concentrations (Galante et al 1994;Asgary et al 2008). In situ hybridization data from the Allen Mouse Brain Atlas show mRNA expression of fibrinogen chains in the mouse brain.…”
Section: Discussionmentioning
confidence: 70%
“…Although this appears to be the first report of fibrinogen level changes in rat brain, human studies have shown that opium users have higher fibrinogen blood concentrations (Galante et al. ; Asgary et al. ).…”
Section: Discussionmentioning
confidence: 81%